2015
DOI: 10.1037/stl0000040
|View full text |Cite
|
Sign up to set email alerts
|

Syllabus length and use of images: An empirical investigation of student perceptions.

Abstract: Although the syllabus is one of the most widely used documents in higher education, research investigating the effectiveness of this tool is minimal. The current study investigates student perception of the course and professor based on the syllabus. A total of 149 students were randomly assigned to one of six syllabus conditions focusing on syllabus length (i.e., short, medium, and long) and the inclusion of images. Participants completed questionnaires and participated in a focus group regarding their percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 12 publications
2
37
4
Order By: Relevance
“…Our findings are unique in the relatively small body of work on syllabus design. While Harrington and Gabert-Quillen (2015) found that images did not change perceptions of faculty, we found that a more visual syllabus design enhanced how participants perceived a hypothetical instructor. These two studies differ, however, in their implementation of a more visual syllabus.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Our findings are unique in the relatively small body of work on syllabus design. While Harrington and Gabert-Quillen (2015) found that images did not change perceptions of faculty, we found that a more visual syllabus design enhanced how participants perceived a hypothetical instructor. These two studies differ, however, in their implementation of a more visual syllabus.…”
Section: Discussioncontrasting
confidence: 67%
“…Few, however, have empirically tested the effects of these design choices. As a rare exception, Harrington and Gabert-Quillen (2015) examined whether the use of images in a syllabus affected student perceptions of the course and instructor. Although they found no effects, their manipulation may not have been sufficiently SYLLABI AND IMPRESSION FORMATION 7 strong, as the images used in this study were not part of a completely modified design strategy (i.e., the two versions of the syllabus tested in this study were fundamentally the same, with the only change being the addition of images to one version).…”
Section: Syllabi and Impression Formationmentioning
confidence: 99%
“…These new scores were also achieved, in part, by eliminating a major assignment description and rubric (ostensibly putting this in a separate document for students). Any interpretation of the higher P and A scores in the revised (and shorter) syllabus must therefore take into consideration that many studies show students prefer more detailed syllabi (Harrington and Gabert-Quillen, 2015).…”
mentioning
confidence: 99%
“…This is particularly important to the GED credentialed student who by nature of their experience would have limited experience with course syllabi (Slattery & Carlson, 2005). As a roadmap, the syllabus must be detailed enough to provide necessary information like due dates and grading rubrics but a review of it during the initial and subsequent class periods could provide greater security for otherwise anxious students (Harrington & Gabert-Quillen 2015).…”
Section: Faculty Course Syllabi Impact Upon Student Persistencementioning
confidence: 99%